1995
DOI: 10.1002/stem.5530130607
|View full text |Cite
|
Sign up to set email alerts
|

Microchimerism, dendritic cell progenitors and transplantation tolerance

Abstract: Abstract. The recent discovery of multilineage donor leukocyte microchimerism in allograft recipients up to three decades after organ transplantation implies the migration and survival of donor stem cells within the host. It has been postulated that in chimeric graft recipients, reciprocal modulation of immune responsiveness between donor and recipient leukocytes may lead, eventually, to the induction of mutual immunologic nonreactivity (tolerance). A prominent donor leukocyte, both in human organ transplant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(85 citation statements)
references
References 108 publications
2
83
0
Order By: Relevance
“…These findings complement older reports that graft-derived dendritic cells (DC) traffic to both draining and systemic lymphoid organs to present alloantigen (43,44). Our studies suggest that secondary lymphoid organs are equally important for the induction of tolerance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings complement older reports that graft-derived dendritic cells (DC) traffic to both draining and systemic lymphoid organs to present alloantigen (43,44). Our studies suggest that secondary lymphoid organs are equally important for the induction of tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…For example, anti-CD40L mAb causes significant and prolonged changes in splenic germinal center architecture (46). More durable approaches to tolerance, such as microchimerism, may also require analysis of lymphoid organ structure (44). Our hypothesis suggests that chimeric interactions in the LN may be germane for tolerance, or that donor CD62L Ϫ/Ϫ hemopoietic cells may be unable to induce tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…19 Furthermore, imDCs can also induce allograft tolerance, suggesting a solution to allograft rejection. 20 TGF-b1 is a key factor during the differentiation of Th cells, which can upregulate Foxp3 expression in Th0 cells, driving them to differentiate into CD4 1 Foxp3 1 Tregs. 16 Here, we successfully transferred the TGF-b1 gene into bone marrowderived imDCs by using adenovirus, and detected a high level of Figure 3 In vitro function of TGF-b1-DCs.…”
Section: Discussionmentioning
confidence: 99%
“…DC that are inherently deficient in cell surface expression of costimulatory molecules can induce T cell hyporesponsiveness in vitro and prolong allograft survival. 24 In this study, we have shown that myeloid DC propagated in vitro with GM-CSF + IL-4 can be transduced using a replication-deficient Ad vector to express the gene encoding CTLA4Ig. This chimeric fusion protein is a potent immunosuppressant that blocks the expression of B7 costimulatory molecules on APC [5][6][7] and that suppresses both experimental allograft rejection [12][13][14][15] and autoimmune disease.…”
Section: Discussionmentioning
confidence: 93%